Gentrification and Displacement: Modeling a Complex Urban Process. Issue 2 (4th March 2019) - Eckerd, Adam; Kim, Yushim; Campbell, Heather
ABSTRACT: To shed some light on longstanding questions around gentrification, in this research we model environmental gentrification and gentrification-related displacement of residents. We do this through the development of an agent-based model of a simple urban region, considering different urban contexts and policy approaches to polluted facilities and the relationship of these policies with subsequent gentrification and displacement. We find that gentrification-related displacement is most likely, and most impactful, in urban regions characterized by high levels of density and low levels of residential segregation preferences. Displacement is far less prevalent in low-density regions, particularly those with high segregation preferences. We discuss the potential for different policy implications in these different urban contexts.